Life beyond the borders: the resistance of the black fungus Cryomyces antarcticus to radiation and space environment - Pacelli, Claudia (Università degli studi della Tuscia - Viterbo, 2017)
Dottorato di ricerca in Ecologia e gestione sostenibile delle risorse ambientali Our understanding of potential life in extraterrestrial environment and its biosignature has mainly focused on studying extreme environments on Earth. Terrestrial extreme environments, indeed, offer a rich source of information allowing us to determine how extreme conditions affect life and molecules associated. Extremophilic organisms, inhabiting these environments, have adapted to the most stunning conditions on Earth environments; among these, the Antarctic cryptoendolitic black fungus Cryomyces antarcticus, isolated in Antarctica, is one of the most resistant eukaryotic microorganism known to date, survived over 1.5 years real space during the LIFE experiment. In the frame of different astrobiological projects (BIOMEX and STARLIFE), the fungus was exposed to different kind of stressors, including vacuum, temperature ranges, Martian atmosphere, simulated space conditions and even real space exposure, which included various types of space-relevant radiations, as part of the cosmic radiation environment. The role of the melanin, a pigment composing the fungal cell wall, in the photo-protection was investigated and demonstrated, by comparing melanized and non-melanized strain of the fungus; melanin as biosignature molecule was analyzed too. In conclusion, this research demonstrated the strong endurance of the Antarctic cryptoendolitic black fungus Cryomyces antarcticus in simulated and real space conditions contributing to our knowledge on the limits of life on Earth, on the potential survival of this eukaryotic microorganism on other planets and to the identification of biosignatures for searching life beyond Earth. La ricerca di vita in ambiente extraterrestre si basa principalmente sullo studio dei microorganismi estremofili, che sono adattati a vivere negli ambienti più estremi della Terra e ci offrono informazioni su come la vita e le molecole ad essa associata siano affette da queste condizioni estreme, per qualsiasi altro tipo di organismo vivente. I microrganismi estremofili sono ben adattati a questi ambienti: tra questi, il fungo nero criptoendolitico Cryomyces antarcticus, isolato in Antartide, è uno degli eucarioti più resistenti conosciuti fino ad oggi. All’interno di due differenti progetti (BIOMEX e STARLIFE), questo fungo è stato esposto a diversi tipi di stress, tra cui vuoto, estremi di temperatura, atmosfera Marziana e perfino reale esposizione a condizioni spaziali sulla Stazione Spaziale Internazionale. E’ stato irraggiato con diversi tipi di radiazioni, tutte parte dello spettro cosmico e quindi rilevanti per studi di astrobiologia. La resistenza del fungo e di molecole ad esso associate è stata analizzata con approcci colturali, molecolari e spettroscopici. Il ruolo della melanina, pigmento componente fondamentale della parete cellulare del fungo, nella foto-protezione è stato dimostrato, confrontando un ceppo melanizzato con uno non-melanizzato. In conclusione la tesi ha dimostrato una forte resistenza del fungo C. antarcticus a condizioni spaziali reali e simulate, contribuendo ad aumentare la nostra conoscenza sui limiti della vita e le sue origini sulla Terra, sulla potenziale sopravvivenza di questi microorganismi su un altro pianeta e all’identificazione di biofirme, tracce di vita presente o pregressa, utili per le prossime missioni esplorative.